2007
DOI: 10.1016/j.ygyno.2007.09.018
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of primary fallopian tube cancer in the United States

Abstract: Objective. The objective of this study was to report the incidence of primary fallopian tube carcinoma (PFTC) in the United States population and to describe associated demographic and clinical factors.Methods. A total of 3051 PFTC cases diagnosed from 1998 to 2003, reported from population-based cancer registries, were analyzed. Registries contributing data represent 83.1% of the U.S. population. Data are presented by age, race/ethnicity, U.S. census region, stage, histology, grade, and laterality. Trends in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 26 publications
7
62
0
5
Order By: Relevance
“…The U.S. incidence rate of PFTC is 0.41 (Stewart et al, 2007). The vast majority of PFTCs (89%) are unilateral at diagnosis, and about 30% are diagnosed at each localized, regional and distant stages (Stewart et al, 2007). U.S. PFTC rates are similar to those reported from Finland (0.3) (Riska et al, 2003) and Denmark (0.5) (Pfeiffer et al, 1989).…”
Section: Primary Peritoneal and Primary Fallopian Tube Cancerssupporting
confidence: 61%
See 1 more Smart Citation
“…The U.S. incidence rate of PFTC is 0.41 (Stewart et al, 2007). The vast majority of PFTCs (89%) are unilateral at diagnosis, and about 30% are diagnosed at each localized, regional and distant stages (Stewart et al, 2007). U.S. PFTC rates are similar to those reported from Finland (0.3) (Riska et al, 2003) and Denmark (0.5) (Pfeiffer et al, 1989).…”
Section: Primary Peritoneal and Primary Fallopian Tube Cancerssupporting
confidence: 61%
“…In contrast, a study from a UK cancer center examining PPC found that age and tumor characteristics (stage and grade) were similar among ovarian and primary peritoneal tumors (Jaaback et al, 2006). The U.S. incidence rate of PFTC is 0.41 (Stewart et al, 2007). The vast majority of PFTCs (89%) are unilateral at diagnosis, and about 30% are diagnosed at each localized, regional and distant stages (Stewart et al, 2007).…”
Section: Primary Peritoneal and Primary Fallopian Tube Cancersmentioning
confidence: 94%
“…White, non-Hispanic women with age of 60~79 years had the highest incidence rate (P< 0.0001). The majority (88%) of PFTCs were adenocarcinomas, of which serous adenocarcinomas accounted for 44% and endometrioid adenocarcinomas for 19% (Stewart et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Then patient addressed to oncology department for adjuvant chemotherapy. published in 2007 involving 3051 cases reported from the cancer registry in the USA between 1998 and 2003, reported an incidence of 4.1 per million women per year [9]. In Finland the incidence is 5.4 per million between 1993 and 1997 [10].…”
Section: Cases Reports Casementioning
confidence: 99%
“…The true incidence is certainly underestimated. Indeed, the diagnosis can be made wrongly as ovarian cancer, it is during the initial surgery or during the examination and pathology [9,10]. Primary fallopian tube cancer is associated with chronic tubal inflammation, infertility, tuberculous salpingitis and tubal endometriosis [5], it is particularly common in familial forms of breast/ovarian cancer, especially in women with constitutional mutation BRCA 1-2 [11].…”
Section: Cases Reports Casementioning
confidence: 99%